Numerical study of the role of mortar joints in the bond behavior of FRP-strengthened masonry - Ghiassi, Bahman (2013)
The performance of the interface between FRP and masonry is one of the key factors affecting the behavior of strengthened masonry elements. Therefore, a sound understanding of the interface behavior is crucial at the design stage. In this paper, the effect of mortar joints in the bond behavior of FRP-strengthened masonry prisms is investigated through numerical modeling. The numerical simulation is performed by adopting a nonlinear three-dimensional micro-modeling approach. Different smeared crack models are considered, and the results are compared in terms of local stress and strain distributions, global force–slip response, and cracking pattern. The accuracy of the FE predictions have been assessed by comparing the results with test data and it was found that three-dimensional FE modeling combined with a rotating smeared crack approach gives the best results, both at local and global levels. Finally, the numerical results obtained considering the presence of mortar joints with different mechanical properties are presented and critically discussed.